2022
DOI: 10.1186/s42234-022-00102-1
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic innervation of human and porcine spleens: implications for between species variation in function

Abstract: Background The vagus nerve affects innate immune responses by activating spleen-projecting sympathetic neurons, which modulate leukocyte function. Recent basic and clinical research investigating vagus nerve stimulation to engage the cholinergic anti-inflammatory pathway (CAP) has shown promising therapeutic results for a variety of inflammatory diseases. Abundant sympathetic innervation occurs in rodent spleens, and use of these species has dominated mechanistic research investigating the CAP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…However, one limitation of our study was that, by using NF-H as a general neuronal marker, we did not identify the types of nerve fibers inside the spleen. This type of nerve-immune interaction (demonstrated by high-resolution microscopic imaging) inside the spleen has been observed in some studies by other investigators ( 72 , 114 116 ). For example, Kirkland et al.…”
Section: Neuroimmune Interactions In Secondary Lymphoid Tissue/organssupporting
confidence: 74%
See 3 more Smart Citations
“…However, one limitation of our study was that, by using NF-H as a general neuronal marker, we did not identify the types of nerve fibers inside the spleen. This type of nerve-immune interaction (demonstrated by high-resolution microscopic imaging) inside the spleen has been observed in some studies by other investigators ( 72 , 114 116 ). For example, Kirkland et al.…”
Section: Neuroimmune Interactions In Secondary Lymphoid Tissue/organssupporting
confidence: 74%
“…This type of nerve-immune interaction (demonstrated by high-resolution microscopic imaging) inside the spleen has been observed in some studies by other investigators (72,(114)(115)(116). For example, Kirkland et al have shown the close association of TH + sympathetic fibers with CD3 + T cells in the human and porcine spleen (72). In addition, Murray et al have also demonstrated close associations between TH + (sympathetic)/ ChAT + (parasympathetic) nerve fibers with CD3 + T cells in the murine spleen (73).…”
Section: Neuroimmune Interactions In the Spleensupporting
confidence: 72%
See 2 more Smart Citations
“…The findings with the spleen discussed by Wulf and Tom [225] is interesting as like bone, tissues of the immune system are disseminated throughout the body, operate in different environments, and are innervated [226][227][228][229]. The spleen [230,231], the lymph nodes [232], the gut mucosal immune system [233,234], the thymus [235], and the bone marrow [236] are all innervated, and the innervation plays a regulatory role. Innervation of tissues, such as the spleen, exhibit some speciesspecific innervation differences [231], and in rodents, the integrity of some immune system components, but not all, can decline with age [235].…”
Section: Is There a Role For Neural Regulation Dysfunction During Bon...mentioning
confidence: 94%